INCREASING THE EFFICIENCY OF PROCESSING HOLES IN CAST IRON BODY PARTS BY DEFORMATION BROACHING - ZAIKA, SERHII; ZAIKA, ANDRII; LYSENKO, OLEKSANDR; SKIBINSKYI, YAROSLAV (Herald of Khmelnytskyi National University. Technical sciences, 2025)
To increase the efficiency of the metalworking industry, it is necessary to develop and implement new resource- and energy-saving technologies in production. One of the directions for solving this problem is the implementation of technological processes that include the operation of deformation broaching, which, in comparison with traditional processing processes, allows significantly improving quality and reducing cost. Therefore, determining the possibility of using the deformation broaching process for processing unevenly rigid parts such as body parts made of low-plastic materials is an urgent task. The deformation broaching process is effectively used in the processing of plastic materials, but for the processing of low-plastic materials, such as cast iron, there are no sufficient recommendations for their use. This can be explained by the fact that their small plasticity resource did not attract the attention of specialists in deformation broaching. This state of affairs is explained by the fact that plasticity, as a property of the material, was perceived either as an unchanging value or as a value that can only decrease. The article analyzes the possibility of increasing the efficiency of processing holes in cast iron body parts by the method of deformation broaching based on the study of the features of the mechanics of interaction of the tool with the product. Based on the results of the research, a new design of the tool for finishing the hole in the hydraulic booster body was proposed and an experimental sample of the deformation broaching was manufactured. The tool was studied in experimental tests. The possibility and feasibility of using deformation broaching for finishing high-precision holes in non-uniformly rigid 9+body parts was proven.
Keywords: finishing; deformation broaching; unevenly rigid body parts; cutting tools